Angiotensin Converting Enzyme Gene Polymorphism in Turkish Asthmatic Patients - CEYHAN, BERRİN; AVŞAR, MELİKE (TAYLOR & FRANCIS INC, 2009)
Asthma is a chronic inflammatory disease of the airways. Several candidate genes have been identified with a potential role in the pathogenesis of asthma, including the angiotensin converting enzyme (ACE) gene. We aimed to investigate the frequency of an ACE gene polymorphism in Turkish asthmatic patients and to determine its impact on clinical parameters and disease severity. Ninety-seven asthmatic patients (M/F 25/72, mean age 39 13 years) and 96 healthy subjects (M/F 26/70, mean age 38 12 years) were included. At baseline, all participants completed a questionnaire on demographics, symptoms, triggering factors, severity of asthma, and the presence of atopism. Blood samples were obtained from all patients and genomic DNA was isolated. The frequency of the ACE genotypes (I = insertion and D = deletion) among asthmatics and controls were compared: asthmatics showed a 40.2% prevalence of the DD genotype (n = 39), ID was 45.4% (n = 44), and II was 14.4% (n = 14.4). In the control subjects, the frequency of DD was18.8% (n = 18), ID was 50% (n = 48) and II was 31.3% (n = 30). The DD ACEgenotype was significantly more frequent in asthmatics compared with controls (p 0.001). Asthmatics with the ID ACE genotype showed a higher frequency of drug allergies, although this was not statistically significant (p = 0.08). Asthmatics with the DD genotype appeared to have a higher incidence of asthmatic episode exacerbations due to viral infections, but again this was not statistically significant (p = 0.08). Patients with mild or moderate-severe asthma had similar frequencies of these mutations. We found a higher frequency of the ACE DD gene mutation in Turkish asthmatic patients compared with non-asthmatics, suggesting that this ACE gene polymorphism may be a risk factor for asthma but does not increase the severity of the disease.
Keywords: angiotensin converting enzyme gene polymorphism; asthma; disease severity; DELETION POLYMORPHISM; HIGH-FREQUENCY; ACE; ASSOCIATION; ATOPY; PREVALENCE; CHILDREN; SYSTEM; TISSUE; COUGH